Comparative effectiveness of switching to alternative tumour necrosis factor (TNF) antagonists versus switching to rituximab in patients with rheumatoid arthritis who failed previous TNF antagonists: the MIRAR Study. Issue 11 (26th June 2012) - Gomez-Reino, Juan J; Maneiro, Jose Ramon; Ruiz, Jorge; Roselló, Rosa; Sanmarti, Raimon; Romero, Ana Belen
Abstract : Objective: To compare the effectiveness of switching to rituximab (RTX) with switching to alternative tumour necrosis factor (TNF) antagonists in patients with rheumatoid arthritis (RA) failing on TNF antagonists. Methods: A multicentre prospective 3-year observational study was performed in patients with RA treated with RTX or an alternative TNF antagonist. The baseline 28-joint disease activity score (DAS28) and Health Assessment Questionnaire (HAQ) score were compared with 6, 9 and 12 month values, adjusting for propensity score quintiles. Propensity scores were estimated for each patient using logistic regression with treatment as the dependent variable and baseline prior number of TNFs >1, years from diagnosis >5, extra-articular manifestations, previous toxicity, use of ≥2 disease-modifying antirheumatic drugs, age and sex as independent variables. Results: 1124 patients were treated with either RTX (n=591, 52.6%) or alternative TNF antagonists (n=533, 47.4%). RTX-treated patients had longer disease duration (p=0.0001), larger numbers of previous TNF antagonists (p<0.0001) and tender and swollen joints (p<0.0001). There was no significant difference in the reduction in DAS28 at 6, 9 and 12 months between RTX-treated patients and those treated with TNF antagonists. However, the reduction in DAS28 was significantly different between RTX-treated patients and adalimumab/infliximab-treated patients (p=0.001 and p=0.05, respectively). There was a marginally significant difference at any time period in the proportion of patients achieving an improvement in the HAQ score of >0.22 (p=0.06). Conclusions: Optimal treatment for patients with RA failing on treatment with TNF antagonists may include RTX. This study suggests that the improvement in DAS28 is larger in patients treated with RTX than in those treated with monoclonal anti-TNF agents.